2016
DOI: 10.1002/hed.24399
|View full text |Cite
|
Sign up to set email alerts
|

Modified endoscopic transnasal‐transmaxillary‐transpterygoid approach to parapharyngeal space tumor resection

Abstract: The MENMAP approach is a viable alternative for removing parapharyngeal space tumors, as it is safe, feasible, and less invasive. © 2016 Wiley Periodicals, Inc. Head Neck 38: 933-938, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…8,10,15,18 Meanwhile, with the evolution of endoscopic skull base surgery, the transnasal approach has also been adopted to manage lesions in the PPS. 9,11 The endoscopic transnasal TP approach can provide a direct route to the upper PPS, but it has also some drawbacks, such as a long and narrow surgical corridor, constricted lateral exposure, limited inferior access, and Eustachian tube resection when extended surgical exposure is needed. 13 The trajectory of the endoscopic transnasal TP approach to the upper PPS is restricted laterally by the medial and lateral pterygoid muscles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,10,15,18 Meanwhile, with the evolution of endoscopic skull base surgery, the transnasal approach has also been adopted to manage lesions in the PPS. 9,11 The endoscopic transnasal TP approach can provide a direct route to the upper PPS, but it has also some drawbacks, such as a long and narrow surgical corridor, constricted lateral exposure, limited inferior access, and Eustachian tube resection when extended surgical exposure is needed. 13 The trajectory of the endoscopic transnasal TP approach to the upper PPS is restricted laterally by the medial and lateral pterygoid muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, endoscope-assisted TO (with or without surgical robotic system) and transnasal transpterygoid (TP) approaches have been used to remove benign lesions of the PPS with reduced surgical complications and cosmetic deformity relative to traditional external approaches. [8][9][10][11] Because of anatomical complexity with important neurovascular structures in the PPS, minimally invasive approaches to this region require detailed and precise anatomic knowledge. Although many operative procedures and endoscopic anatomy of the PPS have been reported, the target area in these investigations is only focused on upper or lower PPS.…”
Section: Introductionmentioning
confidence: 99%
“…Transnasal endoscopic access by means of a transpterygoid approach allows access to the upper part of the PPS . Wasano et al have described the modified endoscopic transnasal‐transmaxillary‐transpterygoid approach, in which the surgical corridor to the PPS consists of the maxillary sinus, submucous tunnel under the lateral nasal wall, and the space created by removing the pterygoid process. This deep region has traditionally been approached through open lateral or anterior approaches, which are associated with several significant complications .…”
Section: Surgerymentioning
confidence: 99%
“…Traditionally, tumors arising from the PPS have been managed through a variety of lateral approaches, including transcervical, transoral, mandibular swing, transparotid, transmastoid, and infratemporal fossa (ITF) approaches and their combinations [4,5]. Increasing literatures have presented the application of endoscopic endonasal surgery in managing lesions involving the upper PPS, with the advantage of reducing the incidence of functional and cosmetic morbidity related to open approaches [6,7]. Van Rompaey et al demonstrated that an endoscopic transmaxillary/transpterygoid approach provided a sufficient surgical window for tumor extirpation, obviating some of the morbidity associated with an open procedure; however, this approach was limited by its access to the petrous portion of the internal carotid artery (ICA) [2].…”
Section: Introductionmentioning
confidence: 99%